NARASI PEMBERITAAN ANIES BASWEDAN PASCA DEKLARASI PENCALONAN PRESIDEN 2024 DI DETIK.COM: KAJIAN ANALISIS WACANA KRITIS - Mad Yahya; Ilham Syafii; Adji Pratama Putra (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2023)
This article aims to analyze the news regarding Anies Baswedan after the declaration of the presidential nomination by the NasDem Party based on Norman Fairclough's critical discourse analysis approach. The data source comes from news related to Anies Baswedan in the online news media Detik.com. Documentation techniques were used in this study through observing, taking notes, and capturing screens. The data is in the form of the title and text of Anies Baswedan's news coverage on the online media Detik.com for two months, namely between 03 October 2022 and 03 December 2022. The results of data identification at the textual level and discourse practice show a tendency that is not neutral in reporting on Anies Baswedan. Reports on the online media Detik.com tend not to support Anies Baswedan in his candidacy for the 2024 presidential election and favor other figures. On the dimension of sociocultural practice, news production related to Anies Baswedan on Detik.com is related to situational aspects and the institutional background of the media. In addition, Indonesia's social and political context after the 2017 DKI Jakarta gubernatorial election and the 2019 presidential election influenced Anies Baswedan's opinion as an opposition figure to President Jokowi's government, which was supported by the Partai Demokrasi Indonesia Perjuangan.